The sketch nation: psychological evaluation of architectural appreciation through the means of urban sketching towards increasing public awareness of sustainable development - Ahmad Hilmy, Ahmad Hakym; Abd Rahman, Khairul Aidil Azlin; Mohd Yunos, Mohd Yazid; Utaberta, Nangkula (Universiti Putra Malaysia Press, 2020)
The theme of the research will resolve around the two main subject, the art of urban sketching and architectural narrative through the study of psychology, philosophy and anthropology. The title is suggesting a development of the ‘sketch nation’ as a way to increase architectural appreciation and awareness on sustainable development of the public societies by engaging them with the sketching culture in their community. In this way, they will be more aware of their surrounding & social responsibilities towards a better approach of Sustainable Development Goals (SDG) coined by the United Nation (UN). The research concentrates on how does urban sketching relates to develop the knowledge of architecture in public societies towards increasing awareness of sustainable development. The evaluation is done through analyzing theory of perception in cognitive psychology and cross-referencing it with the ‘urban sketching manifesto’ to understand the process of how an urban sketcher absorbs their surrounding while sketching in an architectural setting as well as understanding how an architectural built informs the end ends user to highlight on the efforts implemented for sustainable development.